(untitled) - Smith, Ralph J. (New York, 1984)
This book is also available through the Introductory Engineering Custom Publishing System. If you are interested in creating a course-pack that includes chapters from this book, you can get further information by calling 212-850-6272 or sending email inquiries to engineerjwiley.com. The authors offer a set of objectives at the beginning of each chapter plus a clear, concise description of abstract concepts. Focusing on preparing students to solve practical problems, it includes numerous colorful illustrative examples.
Keywords: Electrical engineering,Kỹ thuật điện